2018
DOI: 10.15270/54-2-634
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Lived Experiences of Seasonally Unemployed Parents in the Gouda Area

Abstract: The aim of this qualitative study was to explore and describe the lived experiences of seasonally unemployed parents in the Gouda area of the Western Province. Positive psychology provided the theoretical framework. A qualitative descriptive research design was used and seven adult parents were selected purposefully. Thematic data analysis focused on the inductive coding of collected data. Findings indicate that seasonally unemployed parents experience periods of employment and unemployment as distinctly diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Other South African studies confirmed spiritual practices as the source of resilience in low -and middle–income communities (Van Breda, 2016), enhancing beliefs that safeguard families from the harmful effects of exposure to violence (Isaacs et al, 2020). Izaks et al (2018) also provide a focus on families using spiritual strengths and prayers to cope with the negative effects of seasonal unemployment. Very recent literature demonstrates the renewed use of spirituality as a coping mechanism since the COVID-19 pandemic by people facing possible employment changes and adversity (Burton et al, 2023; O’Connor et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other South African studies confirmed spiritual practices as the source of resilience in low -and middle–income communities (Van Breda, 2016), enhancing beliefs that safeguard families from the harmful effects of exposure to violence (Isaacs et al, 2020). Izaks et al (2018) also provide a focus on families using spiritual strengths and prayers to cope with the negative effects of seasonal unemployment. Very recent literature demonstrates the renewed use of spirituality as a coping mechanism since the COVID-19 pandemic by people facing possible employment changes and adversity (Burton et al, 2023; O’Connor et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Various factors contribute to the rising unemployment rate such as a poor economy, corruption, and skills mismatch (Department of Labour, 2019; Du Toit et al, 2018; Plagerson et al, 2019), resulting in a protracted social crisis. Several research studies have highlighted the negative impact of unemployment on families, which poses an immediate threat to their well-being and functioning (Izaks et al, 2018; Khumalo et al, 2012; Makiwane et al, 2017; Theron & Phasha, 2015). With the arrival of the COVID-19 pandemic (World Health Organization, 2020), the situation worsened, resulting in many more people losing their jobs.…”
Section: Introductionmentioning
confidence: 99%